FACTORS AFFECTING PRENATAL DISTRESS IN BANYUMAS REGENCY AREA - Ulfah, Mariah; Yusuf, Munawir; Mulyani , Sri; Widiyanto (LPPM Universitas Duta Bangsa Surakarta, 2023)
Pregnancy is a series of dramatic events experienced by women, and this can affect them both physically and psychologically. Psychological issues might arise during the prenatal period. The objective of the study was to determine the factors affecting prenatal mental health. The study methods used a cross-sectional with chi square data analysis. The results revealed that pregnancy status affected anxiety, mother's age, pregnancy status, and gestational age affected stress, and mother's age and pregnancy status affected depression.